Inflation and Growth in China. (International Monetary Fund, 1996)
The linkage between inflation and economic growth has been the subject of considerable interest and debate. The 18 papers included in this volume comprise the proceedings of a conference on inflation and growth in China that brought together academics, officials and IMF staff members. The papers edited by Manuel Guitian and Robert Mundell, examine issues in international exeperiences with inflation and growth, long-run and short-run structural problems related tgo growth and inflation in China, and the framework in which monetary, fiscal, and exchange rate policies are formulated in China.